Bibliometric analysis and landscape of actors in passive cooling research. (October 2021) - Miranda, Nicole D.; Renaldi, Renaldi; Khosla, Radhika; McCulloch, Malcolm D.
Abstract: This paper presents the trends and actors from research publications covering passive cooling technologies. The unprecedented growth in the provision of cooling is posing a significant risk to energy systems and the natural environment, making passive cooling an important alternative to air conditioners. This paper provides a first necessary step towards better understanding the contribution of passive cooling. By conducting a bibliometric analysis on passive cooling technologies, first, it identifies the relevant literature through structured searches. Second, it examines the actors in the field (i.e. countries, authors, research communities and funders). Further, the main researchers by specific passive cooling categories are analysed in detail in terms of the trajectory of publication and author clusters, including novel visualisations of productivity and collaboration. The search results in a set of 2, 859 unique documents, to our knowledge, the largest set in the subject. The country most named in affiliations is the United States ( N = 762 ), but since 2010, China ( N = 544 ) has driven a rapid increase in research activity. Specific technologies also show increasing trends in annual publications, with natural ventilation being the dominant passive cooling measure ( N = 389 ), followed by microclimate ( N = 317 ) and radiative cooling ( N = 312 ) . In the last three years, however, publications on radiative cooling and solar control have been the most numerous and hence are promising technologies in the field. The top publishing author is M. Santamouris within a community of 41 researchers covering most technologies. Other top authors (e.g. L. F. Cabeza and S. Herkel) and their communities are also found to research multiple cooling technologies. Research in the field is currently expanding as observed by top communities mainly publishing from 2010. Only five of the main research clusters were established before 2000s. The majority of funding and support identified has come from the public sector such as grants from the European Union, national ministries or scientific budgets. This paper provides new insights on passive cooling research to date, for promoting scientific collaboration, informing decision-makers and structuring the literature. Highlights: The largest set of publications on passive cooling is systematically compiled. Meta-data is examined by bibliometric analysis. Passive technologies are analysed by year, countries and authorship. Research networks and communities of collaborations are identified.